Clean production of carbon nanomaterials to remove arsenic from drinking water - Al-Mamun, Abdullah; Yehya, M. Ahmed; Mohammed, A. R. S.; Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Al-Khatib, Ma'an Fahmi Rashid; Ismail, Ahmad Faris; Idris, Azni (Ontario International Development Agency, 2010)
Novel carbon nanomaterials (CNM) were synthesized through a chemical vapour deposition (CVD) process to adsorb arsenic (As) from water. Iron (Fe) and Nickel (Ni) catalysts were used to produce two different types of CNM, namely carbon nanotubes (CNT) and carbon nanofibres (CNF). Powdered activated carbon (PAC) was used as a substrate, which played the key role for a less hazardous and clean production of CNM. Various concentrations of As (0.5, 5.0 and 10.0 mg/L) were used to prepare synthetically polluted drinking water, which was used for batch mode adsorption experiments in shake flasks. Adsorption capacities for CNF at respective concentrations were 1.46, 13.78, 27.97 mg/g and 1.86, 18.44 and 19.68 mg/g for CNT. Results showed that the CNT was suitable for low concentration of arsenic while CNF was good for high concentration. Two isotherms were studied for arsenic removal. It was observed that the CNT fitted better for Langmuir model with the correlation coefficient of 0.967, while Freundlich worked better for the CNF exhibiting correlation coefficient of 0.999